2002
DOI: 10.1016/s0969-2126(01)00695-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Anthocyanidin Synthase from Arabidopsis thaliana

Abstract: Flavonoids are common colorants in plants and have long-established biomedicinal properties. Anthocyanidin synthase (ANS), a 2-oxoglutarate iron-dependent oxygenase, catalyzes the penultimate step in the biosynthesis of the anthocyanin class of flavonoids. The crystal structure of ANS reveals a multicomponent active site containing metal, cosubstrate, and two molecules of a substrate analog (dihydroquercetin). An additional structure obtained after 30 min exposure to dioxygen is consistent with the oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
294
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(319 citation statements)
references
References 45 publications
14
294
0
1
Order By: Relevance
“…If, as previously proposed, C-3 oxidation is the initial step in catalysis (48,49), together with (i), this is consistent with a mechanism in which the initially introduced hydroxyl group is subsequently lost.…”
Section: O Environments and Mechanistic Insights Into The 2og-dependesupporting
confidence: 86%
See 1 more Smart Citation
“…If, as previously proposed, C-3 oxidation is the initial step in catalysis (48,49), together with (i), this is consistent with a mechanism in which the initially introduced hydroxyl group is subsequently lost.…”
Section: O Environments and Mechanistic Insights Into The 2og-dependesupporting
confidence: 86%
“…Recent crystallographic work has demonstrated that ANS contains the double-stranded ␤-helix common to other 2OG oxygenases and identified the residues involved in substrate binding (38,48).…”
mentioning
confidence: 99%
“…2B). Based on the crystal structure of similar proteins, the LBO catalytic domain contains hallmark amino acid residues His-235, His-293, and Asp-237 for iron binding and Arg-303 for substrate interaction (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…This Escherichia coli protein is a member of a rapidly expanding enzyme superfamily that utilizes mononuclear Fe(II) active sites to catalyze a diverse range of chemical transformations, usually coupled to the oxidative decarboxylation of an ␣-keto acid (2)(3)(4). Other family members include enzymes that modify protein side chains (5,6), repair alkylation-damaged DNA (7), degrade compounds in the environment (8)(9)(10)(11), and synthesize antibiotics (12)(13)(14), plant metabolites (15,16), or other small molecules (17,18). Most representatives carry out specific hydroxylation reactions, but examples of enzymes catalyzing desaturations, ring closures, and ring expansion reactions have also been documented (19).…”
mentioning
confidence: 99%